STUDI KELAYAKAN USAHA BINATU DI KOTA AIRMADIDI KABUPATEN MINAHASA UTARA - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 6 No.1, 2007 JBE UNKLAB, 2007)
Laundry Business Prospect in Airmadidi, North Minahasa is very good. The survey found that there is only one such business exist currently, located in Kawiley village. Majority of customers may come from dormitory and non-dormitory students far from the campus to be able to get adequate earnings.